Wicked problems in practice: Responding to ecological transformation in wilderness - Jaclyn Fox Rushing; Kira Hefty; Teresa N. Hollingsworth; Amanda E. Cravens; Christopher A. Armatas; Clare Boerigter; Kellie J. Carim; Shelley D. Crausbay; Olga Helmy; David J. Lawrence; Lauren Redmore; Gregor W. Schuurman; et al. (Ambio, 2026)
Congressionally designated wilderness offers the highest level of land protection in the USA, comparable to category 1b wilderness as defined by the International Union for Conservation of Nature, yet wilderness areas face impacts of climate change. Researchers and managers increasingly recognize the immense challenge of stewarding wilderness in a changing climate. Although responding to climate change is considered a wicked problem, this framing has not been applied to wilderness contexts. We move theory into practice by using wicked problem framing and four illustrative cases to explore how the resist–accept–direct (RAD) framework can help untangle the wicked problem of addressing unprecedented ecological transformation in wilderness. The RAD framework clarifies a range of response options including resisting transformation, accepting it, or directing it toward preferred new conditions. As climate change continues to challenge wilderness managers, the RAD framework can help assess trade-offs and preserve wilderness character into the twenty-first century.

Evaluating MXene-doped PEDOT coating on carbon fiber microelectrodes for dual-functional neural interfacing - Sorel E. De León; Rana Jaylani; Young Jun Jung; Negin Jalilinejad; Toon Goris; Simon Higham; Kate Fox; Michael Ibbotson; Steven Prawer; Shadi Houshyar; Wei Tong; David J. Garrett (Analytica Chimica Acta, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Stable Isotope Ecology of the Early Miocene Rusinga Island Mammalian Communities from the Hiwegi and Kulu Formations (Nyanza Province, Western Kenya) - David L. Fox; Nicole D. Garrett; Daniel J. Peppe; Lauren A. Michel; Kirsten Jenkins; Thomas Lehmann; Kieran P. McNulty (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Cross-national comparison of the restorative potential of urban forests in different seasons - Xiaohao Yang; David Grace; Chongxian Chen; Derek Van Berkel; Nathan Fox; Mark Lindquist (Landscape and Urban Planning, 2025)

Co-disposal of wood ashes and mine wastes to control acid and metalliferous drainage - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Environmental Research, 2025)

Citizen scientists as butterfly predators: using foraging theory to understand individual recorder behaviour - Mingrui Li; Robin J. Boyd; Chloë Smith; Richard Fox; David Roy; Jonathan Bennie; Richard H. ffrench-Constant (Ecological Modelling, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Optimal placement and coordinated scheduling of distributed space-based lasers for orbital debris remediation - David O. Williams Rogers; Matthew C. Fox; Paul R. Stysley; Hang Woon Lee (Advances in Space Research, 2025)

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

Evaluation of the WEPS hydrology sub-model for surface soil water content under different tillage practices in the inland Pacific Northwest, USA - Huawei Pi; David R. Huggins; Larry.E. Wagner; Fred. Fox; Sisi Li; Nicholas P. Webb (CATENA, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Identifying biomarkers for shifts in microbial community structure in Irish Grasslands: the influence of context-specific drivers - Aaron Fox; Ana Barreiro; David Wall; Giulia Bondi (Journal of Soils and Sediments, 2025)
Purpose This study investigated the comparative influence of regional/climatic difference in agronomic potential (‘Region'), natural drainage (‘Drainage’) and grassland management intensity (‘Manage’) on soil physicochemical variables, microbial community structure and soil potential extracellular enzymatic activity across 37 Irish grassland sites. Methods Soil samples were collected in a structured manner from representative sites, and soil physicochemical parameters were measured. Soil microbial community structure was determined by phospholipid fatty acid analysis and different potential soil extracellular enzymatic activities were measured through both fluorometric and colorimetric assays. Doubly-nested PERMANOVA and ANOVA models were performed in R to evaluate the impact of the examined factors on multivariate and univariate variables, respectively. Results A doubly-nested PERMANOVA model revealed that each of the three factors exerted a significant influence on soil microbial community structure ( p < 0.05). The factor ‘Drainage’ did have a stronger influence on the abundance of the fatty acid biomarker for the arbuscular mycorrizal fungi (effect size = 20.54%) than ‘Region’ had (effect size = 10.05%), with ‘Manage’ having no significant effect. In contrast to soil microbial community structure, individual soil potential extracellular enzymatic activities mostly either did not significantly respond to any factor, or significantly responded to ‘Region’ only ( p < 0.05, i.e., β-N-acetyl-glucosaminidase, arylsulfatase and acid phosphatase). Conclusion The study highlights the value of considering localized environmental drivers in studies relating to soil parameters at the national level, to support effective, context-specific management strategies for soil biodiversity conservation and national monitoring schemes of soil biology.

Heterotrophy of particulate organic matter subsidies contributes to divergent bleaching responses in tropical Scleractinian corals - Connor R. Love; Kelly E. Speare; Michael D. Fox; Veronica Z. Radice; Kelton W. McMahon; Gretchen E. Hofmann; David L. Valentine; Marie E. Strader (Limnology and Oceanography, 2025)
Heterotrophic feeding on plankton and particulate organic matter (POM) by tropical Scleractinian corals is known to aid in the resistance and recovery from thermally induced bleaching. However, the relative importance of heterotrophy in promoting bleaching resistance and recovery is likely to vary based on ecological context and the severity of heat stress. In 2019, the Pacific Island of Mo'orea experienced mass coral mortality during a widespread marine heatwave. Many Acropora hyacinthus colonies on the shallow reef slope (5 m) were resistant to bleaching, while colonies on the deeper fore reef (14 m) often bleached and subsequently recovered, despite similar thermal stress. The role of heterotrophy in this divergent bleaching response was investigated using fatty acid (FA), isotopic, and elemental biomarkers. Multiple complementary lines of evidence, including feeding proxies, isotopic niche overlap, and putative POM FA biomarkers, indicated that bleaching resistant colonies were likely consuming more POM than their bleached and recovered counterparts. Additionally, although visually recovered, host energetics in recovered colonies remained compromised and exhibited proportionally less monounsaturated and polyunsaturated FAs and less relative nitrogen than resistant colonies. We show that corals that rely more on heterotrophic nutrient acquisition can better resist thermally induced bleaching. Our results also revealed the long‐term energetic costs of bleaching even after visual recovery. Ultimately, these results underscore the vital role of coral nutrition in shaping coral bleaching response and recovery.

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Mineralogical and geochemical characterization of mine tailings in the King river delta, Western Tasmania: Implications for long-term stability of trace elements - Sibele C. Nascimento; David R. Cooke; Matthew J. Cracknell; Clare B. Miller; Anita Parbhakar-Fox (Applied Geochemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Establishing performance criteria for evaluating watershed-scale sediment and nutrient models at fine temporal scales - Aayush Pandit; Sarah Hogan; David T. Mahoney; William I. Ford; James F. Fox; Christopher Wellen; Admin Husic (Water Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Using tracking data to assess seasonal habitat use and conflict potential of Greylag Geese in Danish intensive agricultural landscapes - Kevin Kuhlmann Clausen; Lars Dalby; Henning Heldbjerg; Lei Cao; Anthony David Fox (European Journal of Wildlife Research, 2025)

Are increasing roosting waterbird numbers responsible for eutrophication of shallow lakes? Examples from a Danish Ramsar site - Preben Clausen; Torben L. Lauridsen; Claus Lunde Pedersen; Henrik Haaning Nielsen; Erik Jeppesen; Martin Søndergaard; Kees H. T. Schreven; Bart A. Nolet; Jesper Madsen; Anthony David Fox (Hydrobiologia, 2025)
The Water Framework Directive (WFD) requires actions from European Union Member States to reduce external nutrient loading in lakes of moderate/poor/bad ecological status and restore their good ecological status. Several poor-quality Danish lakes have been exempted from WFD criteria (and more proposed), due to suspected major imported nutrient contributions from waterbirds, without supporting evidence. Here, we estimated relative nutrient contributions from increasing numbers of roosting waterbirds compared to total nutrient loadings in four brackish lakes (43–491 ha) at an internationally important Ramsar site/EU Birds Directive Special Protection Area. Combining night- and daytime counts of roosting numbers of the most numerous species with intake and faecal output models, we estimated roosting birds (mostly geese) contributed 0.2–0.4% of all N inputs (0.3–1.2 kg N/ha/year) and 0.6–2.0% of all P inputs (0.04–0.12 kg P/ha/year) in three lakes (one of which has been proposed exempted from WFD criteria), but potentially as high as 14% and 76%, respectively, at a fourth clearwater lake without direct inflow or outlets. These results confirm the need for case-by-case assessments of avian nutrient import relative to total nutrient balance before exempting lakes from WFD conditions due to supposed natural loading from waterbirds.

Response time of fast flowing hydrologic pathways controls sediment hysteresis in a low-gradient watershed, as evidenced from tracer results and machine learning models - Arlex Marin-Ramirez; David Tyler Mahoney; Brenden Riddle; Leonie Bettel; James F. Fox (Journal of Hydrology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Automating avalanche detection in ground-based photographs with deep learning - James Fox; Anna Siebenbrunner; Sandra Reitinger; David Peer; Antonio Rodríguez-Sánchez (Cold Regions Science and Technology, 2024)

Counter‐gradient variation in gene expression between fish populations facilitates colonization of low‐dissolved oxygen environments - Janay A. Fox; David A. G. A. Hunt; Andrew P. Hendry; Lauren J. Chapman; Rowan D. H. Barrett (Molecular Ecology, 2024)
The role of phenotypic plasticity during colonization remains unclear due to the shifting importance of plasticity across timescales. In the early stages of colonization, plasticity can facilitate persistence in a novel environment; but over evolutionary time, processes such as genetic assimilation may reduce variation in plastic traits such that species with a longer evolutionary history in an environment can show lower levels of plasticity than recent invaders. Therefore, comparing species in the early stages of colonization to long‐established species provides a powerful approach for uncovering the role of phenotypic plasticity during different stages of colonization. We compared gene expression between low‐dissolved oxygen (DO) and high‐DO populations of two cyprinid fish: Enteromius apleurogramma , a species that has undergone a recent range expansion, and E. neumayeri , a long‐established native species in the same region. We sampled tissue either immediately after capture from the field or after a 2‐week acclimation under high‐DO conditions, allowing us to test for both evolved and plastic differences in low‐DO vs high‐DO populations of each species. We found that most genes showing candidate‐evolved differences in gene expression did not overlap with those showing plastic differences in gene expression. However, in the genes that did overlap, there was counter‐gradient variation such that plastic and evolved gene expression responses were in opposite directions in both species. Additionally, E. apleurogramma had higher levels of plasticity and evolved divergence in gene expression between field populations. We suggest that the higher level of plasticity and counter‐gradient variation may have allowed rapid genetic adaptation in E. apleurogramma and facilitated colonization. This study shows how counter‐gradient variation may impact the colonization of divergent oxygen environments.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Skin barrier function for regulatory skin absorption tests and effects on testosterone and sucrose absorption - Thomas Brackin; Heather Gayes; Ian Johnson; David Fox; Clive Roper (Toxicology in Vitro, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Biogeographical variation in migratory patterns of palearctic breeding Greater White‐fronted Geese - Junjian Zhang; Xueqin Deng; Qingshan Zhao; Diana Solovyeva; Andrea Kölzsch; Inga Bysykatova‐Harmey; Zhenggang Xu; Yanbo Xie; Helmut Kruckenberg; Lei Cao; Anthony David Fox (Journal of Biogeography, 2024)
Aim Continental comparisons of migration strategies within and between populations of single species are rare but can be insightful to understand key environmental factors shaping differences in migration systems. We investigated differences in stopover networks and migration strategies between three separate Eurasia Greater White‐fronted Geese (GWFG) Anser albifrons populations to better understand how each overcomes the different topographic challenges faced along their migration routes during spring and autumn. Location Eurasia. Taxon Birds. Methods Using 106 (autumn) and 65 (spring) tracks from tagged GWFG from three Eurasian populations (Baltic‐North Sea [BNS] in the west; East Asia Continental [EAC] and West Pacific [WP] in the east), we generated stopover networks, calculated network metrics, quantified migration parameters and compared variation between populations and seasons. Results BNS showed largest network size, shortest average geodesic distance in both seasons, shortest migration distances, most stopover sites, longest stopover duration and shortest step length. EAC showed longest migration distance and second maximal flight length (>1600 km). WP showed shortest migration durations and longest maximal flight length (>2500 km). Summering ground arrival dates did not differ between populations. Autumn migration duration was shorter and migration speed faster than in spring in all populations. Main Conclusions We infer lack of obvious ecological barriers to BNS geese shapes their frequent stopovers of short duration. In contrast, EAC geese face two major ecological barriers (3100 km boreal forest, high mountains, dense human settlement and ocean) and WP geese must pass c. 2400 km of forest, mountains and ocean along their migration corridors, necessitating longer staging and migration segments of greater duration. We conclude that, despite almost identical body plan, all populations respond to radically different topographic challenges, adapting to meet these using different movement strategies, balancing migration schedule and fat accumulation patterns with availability and quality of stopovers.

Increased belowground tree carbon allocation in a mature mixed forest in a dry versus a wet year - Ido Rog; Boaz Hilman; Hagar Fox; David Yalin; Rafat Qubaja; Tamir Klein (Global Change Biology, 2024)
Tree species differ in their carbon (C) allocation strategies during environmental change. Disentangling species‐specific strategies and contribution to the C balance of mixed forests requires observations at the individual tree level. We measured a complete set of C pools and fluxes at the tree level in five tree species, conifers and broadleaves, co‐existing in a mature evergreen mixed Mediterranean forest. Our study period included a drought year followed by an above‐average wet year, offering an opportunity to test the effect of water availability on tree C allocation. We found that in comparison to the wet year, C uptake was lower in the dry year, C use was the same, and allocation to belowground sinks was higher. Among the five major C sinks, respiration was the largest (ca. 60%), while root exudation (ca. 10%) and reproduction (ca. 2%) were those that increased the most in the dry year. Most trees relied on stored starch for maintaining a stable soluble sugars balance, but no significant differences were detected in aboveground storage between dry and wet years. The detailed tree‐level analysis of nonstructural carbohydrates and δ 13 C dynamics suggest interspecific differences in C allocation among fluxes and tissues, specifically in response to the varying water availability. Overall, our findings shed light on mixed forest physiological responses to drought, an increasing phenomenon under the ongoing climate change.

Occupancy trends of overwintering coastal waterbird communities reveal guild‐specific patterns of redistribution and shifting reliance on existing protected areas - Devin R. de Zwaan; Andrew Huang; Caroline H. Fox; David W. Bradley; Danielle M. Ethier (Global Change Biology, 2024)
Climate change and anthropogenic stressors are redistributing species and altering community composition globally. Protected areas (PAs) may not sufficiently protect populations of species undergoing distributional shifts, necessitating that we evaluate existing PAs and identify areas for future protection to conserve biodiversity across regional and temporal scales. Coastal waterbirds are important indicators of marine ecosystem health, representing mobile, long‐lived, higher trophic‐level consumers. Using a 20‐year citizen science dataset (1999–2019) with a before‐after control‐intervention sampling framework for habitat protection, we applied dynamic occupancy models to assess winter occupancy trends along the Pacific coast of Canada. Specifically, we sought to understand potential drivers of regional declines, spatial commonalities among guilds, and changes in habitat use before and after PA designation, as well as between PAs and non‐PAs. Occupancy trends varied regionally, with greater declines in the south compared to the north. Regional differences underlined potential range shifts, particularly for species with traits linked to temperature tolerance, movement, and high productivity foraging, as cold‐tolerant, migratory benthivores and piscivores wintered farther north relative to 20 years ago or retreated to cold‐water fjords. While 21 of 57 (36.8%) species responded positively to PA designation (before‐after), greater occupancy declines tended to occur in PAs established pre‐1999 relative to non‐PAs (control‐intervention). Since PAs are currently concentrated in the south, negative associations were most apparent for species retreating northward, but existing PAs may have a stabilizing or transitory effect on southern wintering species shifting into the region from farther south. We emphasize that conservation strategies must balance persistence of current communities with preserving the climate‐adapted biodiversity of tomorrow by accounting for community‐level effects of species moving into and out of existing PAs. Incorporating range shifts into PA planning by predicting distributional changes will allow conservation practitioners to identify priority habitats, such as cold‐water refugia, for persistent wildlife communities.

Validation of a molecular sex marker in three sturgeons from eastern North America - Nicholas M. Sard; Brian R. Kreiser; Richard M. Pendleton; Barbara A. Lubinski; Robin L. Johnson; Dewayne A. Fox; Joel P Van Eenennaam; Jason E. Kahn; Chris Hager; Amanda L. Higgs; David C. Kazyak (Conservation Genetics Resources, 2024)

Geochemical, mineralogical, and geophysical methods to establish the geoenvironmental characteristics of the King River delta, Queenstown, Western Tasmania - Sibele C. Nascimento; Anita Parbhakar-Fox; Matthew J. Cracknell; David R. Cooke; Clare B. Miller; Wei Xuen Heng (Applied Geochemistry, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Long-Term Impact of Historical Mining on Water Quality at Mount Lyell, Western Tasmania, Australia - Sibele C. Nascimento; David R. Cooke; Ashley T. Townsend; Garry Davidson; Anita Parbhakar-Fox; Matthew J. Cracknell; Clare B. Miller (Mine Water and the Environment, 2023)
During the twentieth century, inadequate management of mine waste at the Mount Lyell Copper Mine affected the ecology of the Queen–King Rivers and Macquarie Harbour, western Tasmania, Australia. Over the past two decades, the water quality of the river system has been measured semi-annually to investigate the long-term hydrochemical and environmental impacts caused by these historical mine practices and the waste associated with the Mount Lyell mine to the Queen–King Rivers. At sample sites below the confluence of Haulage Creek, the water pH was below pH 3.5, remaining below pH 5 across all sites to Macquarie Harbour. Local baseline rivers ranged from pH 4.0 to 8.4. Elemental concentrations of dissolved metals in water samples downstream of Haulage Creek were above the Australian and New Zealand Environment and Conservation Council (ANZECC) water quality guidelines. Copper, Fe, and Zn were not attenuated along the length of the river, with concentrations remaining elevated to the King River Delta. Mineralogical analyses demonstrated secondary minerals in sediments at Haulage Creek and pyrite concentrated at the King River Delta. Static tests on mining-affected sediments indicated risk of AMD and metal(loid) leaching in the river system. Since 2016, after flooding of the Prince Lyell mine, dissolved metal levels in the Queen–King Rivers have decreased; however, concentrations remain above guidelines. Almost three decades after legacy mine waste disposal ended, it still poses a long-term risk to the downstream environment, implying that without effective management of these historical mine wastes, the Queen–King Rivers will continue to be severely impacted. Graphical Abstract

Investigating scent communication and latrine use to inform translocation of the Tasmanian devil - Debra M. Shier; Gregory F. Grether; Elizabeth E. Reid-Wainscoat; Samantha Fox; David Pemberton; Jodie Elmer; Ronald R. Swaisgood (Behavioral Ecology and Sociobiology, 2023)
Translocation programs for endangered mammalian carnivores face numerous challenges, including the potential for lethal interactions between releasees and resident conspecifics. Here we evaluate whether familiarizing residents with the scent of releasees might be an effective strategy for reducing aggression following Tasmanian devil ( Sarcophilus harrisii ) translocation. Tasmanian devils live in loose social networks in which residents have overlapping home ranges and use communal latrines. In a controlled ex situ experiment, we first found that devils readily distinguished between the feces of familiar and unfamiliar conspecifics. Next, we swapped feces between devils slated for release and wild resident devils, seeding a random half of communal latrines in the wild with the feces of releasee prior to their release, and used motion-activated video cameras to record devil visits. Wild resident devil visitation frequency and olfactory communication behaviors initially increased at experimental latrine sites where feces were deposited but not at control sites. After release, the translocated devils used both types of latrine sites and spent more time investigating experimental sites, but investigatory and scent-marking behaviors of the wild resident devils decreased, suggesting that they had become familiar with the releasees through scent. We further show that Tasmanian devil latrine sites are strongly associated with ecotones and the presence of shrubs. These findings contribute to our understanding of Tasmanian devil scent ecology and suggest that devil translocations conducted into existing populations would benefit from familiarization through latrine scent manipulation. More broadly, our results suggest an important role for scent ecology in carnivore translocation programs. Significance statement A conservation management action that is being trialed for endangered Tasmanian devils is to breed devils in human care and reinforce dwindling small resident populations through translocation. However, with limited social interactions, unfamiliar devils may interact aggressively, increasing injury and reducing translocation success. Scent communication is nearly ubiquitous in mammals and may be a prerequisite for management of social aggression. Almost nothing is known about devil scent ecology. Our discovery that devils become familiarized with conspecifics through feces, combined with findings that wild devils that are exposed to translocated devil scent in advance of release show reduced interest in scent-seeded latrines, even after new devils are released, suggests that devils familiarized through scent in advance of relocation may exhibit reduced aggression. These results provide an avenue for improving the success of translocations for devils and other at-risk solitary mammalian carnivores.

Geoenvironmental characterisation of legacy mine wastes from Tasmania – Environmental risks and opportunities for remediation and value recovery - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Journal of Hazardous Materials, 2023)

Alkaline industrial wastes – Characteristics, environmental risks, and potential for mine waste management - Annah Moyo; Anita Parbhakar-Fox; Sebastien Meffre; David R. Cooke (Environmental Pollution, 2023)

Co-alteration Network Architecture of Major Depressive Disorder: A Multi-modal Neuroimaging Assessment of Large-scale Disease Effects - Jodie P. Gray; Jordi Manuello; Aaron F. Alexander-Bloch; Cassandra Leonardo; Crystal Franklin; Ki Sueng Choi; Franco Cauda; Tommaso Costa; John Blangero; David C. Glahn; Helen S. Mayberg; Peter T. Fox (Neuroinformatics, 2023)

Leveraging social science research to advance contemporary rangeland management: Understanding the “new faces” of range managers - David Matarrita-Cascante; Jacob Lucero; Cinthy Veintimilla; Morgan Treadwell; William Fox; Douglas Tolleson (Rangelands, 2023)

Diversity in marine protected area regulations: Protection approaches for locally appropriate marine management - Dominic A. Andradi-Brown; Laura Veverka; Amkieltiela; Nicole L. Crane; Estradivari; Helen E. Fox; David Gill; Jordan Goetze; Charlotte Gough; Nils C. Krueck; Sarah E. Lester; Shauna L. Mahajan; et al. (Frontiers in Marine Science, 2023)
Globally, marine protected area (MPA) objectives have increasingly shifted from a primary focus on maintaining ecosystems through prohibiting extractive activities, to more equitable approaches that address the needs of both people and nature. This has led to MPAs with a diverse array of fisheries restrictions and recent debate on the type of restrictions that contribute to achieving biodiversity goals. Here we use a global dataset of 172 MPAs (representing 31 nations) alongside nine detailed case study MPAs (from Australia, Belize, Cambodia, Federated States of Micronesia, Fiji, Indonesia, Madagascar, Solomon Islands, and United States of America), including partially protected areas that allow regulated fishing, to illustrate the many diverse pathways that some MPAs have adopted to protect biodiversity and safeguard the rights and well-being of resource-dependent coastal communities. We group MPAs based on their restrictions and explore four key insights emerging from these groupings using our nine case studies: (i) MPAs use highly diverse approaches to regulate fisheries; (ii) partially protected areas can address gaps in regional fisheries management; (iii) devolving resource management rights to communities influences the chosen fisheries restrictions; and (iv) state-governed MPAs can use highly tailored fisheries restrictions to increase equity in access. We find that partially protected MPAs can offer effective and equitable pathways for biodiversity conservation if tailored to local context. Rather than focusing primarily on fully protected areas for achieving new global MPA targets, we recommend countries use a blend of locally-appropriate protection levels – from fully protected areas to partially protected MPAs to achieve positive biodiversity outcomes.

Cost-effective screen-printed carbon electrode biosensors for rapid detection of microcystin-LR in surface waters for early warning of harmful algal blooms - Stephanie Stoll; Jae-Hoon Hwang; David W. Fox; Keugtae Kim; Lei Zhai; Woo Hyoung Lee (Environmental Science and Pollution Research, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Large contribution of woody plant expansion to recent vegetative greening of the Northern Great Plains - Bryce Currey; David B. McWethy; Nicholas R. Fox; E. N. Jack Brookshire (Journal of Biogeography, 2022)
Aim Extensive portions of high‐latitude grasslands worldwide have recently experienced increased vegetative productivity (i.e., greening) and have undergone a rapid transition towards woody plant dominance via the process of woody plant expansion (WPE). This raises the underlying question: To what degree are WPE and greening spatiotemporally linked? Given that these vegetative changes are predicted to continue, we seek to understand how recent changes in vegetation extent and productivity have interacted under recent climate change and anthropogenic disturbance to provide insights surrounding the future trajectory of temperate grasslands broadly. Location Northern Great Plains (NGP), North America. Taxon Woody plants. Methods Greening was measured as the significant increase in three metrics between 2000 and 2019: leaf area index (LAI), annual maximum normalized difference vegetative index (NDVI) and annual mean NDVI. WPE was measured as the significant proportional increase in percent tree cover change between 2000 and 2019 in grasslands. We then examined these variables across a host of 26 potential driving variables. Results We show that average proportional greening increased by 0.2–1.3% year −1 (depending on metric), and proportional WPE increased by 6.9% year −1 since 2000 across the NGP. Both changes are largely driven by the absence of wildfire and changing climate. Furthermore, WPE was spatially coherent and positively associated with a large component of recent greening, as revealed by their coupling across 34.1%–40.6% of grassland area and as evidenced by the 9.7%–19.7% of the variability in greening explained by WPE. Main conclusions WPE and greening are spatiotemporally coupled across large portions of the NGP. Under continued climate change and wildfire suppression, WPE and greening are likely to continue across large swathes of grasslands globally. Furthermore, our results show that using a single greening metric may be insufficient to capture the large‐scale vegetative changes such as the expansion of woody vegetation.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cancer microenvironment and genomics: evolution in process - Stanley P. Leong; Isaac P. Witz; Orit Sagi-Assif; Sivan Izraely; Jonathan Sleeman; Brian Piening; Bernard A. Fox; Carlo B. Bifulco; Rachel Martini; Lisa Newman; Melissa Davis; Lauren M. Sanders; et al. (Clinical & Experimental Metastasis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Establishment of a microsatellite genetic baseline for North American Atlantic sturgeon (Acipenser o. oxyrhinchus) and range-wide analysis of population genetics - Shannon L. White; David C. Kazyak; Tanya L. Darden; Daniel J. Farrae; Barbara A. Lubinski; Robin L. Johnson; Michael S. Eackles; Matthew T. Balazik; Harold M. Brundage; Adam G. Fox; Dewayne A. Fox; Christian H. Hager; et al. (Conservation Genetics, 2021)

Trait Response to Nitrogen and Salinity in Rhizophora mangle Propagules and Variation by Maternal Family and Population of Origin - Christina L. Richards; Kristen L. Langanke; Jeannie Mounger; Gordon A. Fox; David B. Lewis (Frontiers in Marine Science, 2021)
Many coastal foundation plant species thrive across a range of environmental conditions, often displaying dramatic phenotypic variation in response to environmental variation. We characterized the response of propagules from six populations of the foundation species Rhizophora mangle L. to full factorial combinations of two levels of salinity (15 ppt and 45 ppt) reflecting the range of salinity measured in the field populations, and two levels of nitrogen (N; no addition and amended at approximately 3 mg N per pot each week) equivalent to comparing ambient N to a rate of addition of 75 kg per hectare per year. The response to increasing salinity included significant changes, i.e., phenotypic plasticity, in succulence and root to shoot biomass allocation. Propagules also showed plasticity in maximum photosynthetic rate and root to shoot allocation in response to N amendment, but the responses depended on the level of salinity and varied by population of origin. In addition, propagules from different populations and maternal families within populations differed in survival and all traits measured except photosynthesis. Variation in phenotypes, phenotypic plasticity and propagule survival within and among R. mangle populations may contribute to adaptation to a complex mosaic of environmental conditions and response to climate change.

The Impact of the Parenteral Opioid Medication Shortages on Opioid Utilization Practices in the Emergency Department of Two University Hospitals - Amanda J. Deutsch; David A. Gajdosik; Christine Ramdin; Collin Tebo; Maryann Mazer-Amirshahi; Erin R. Fox; Josh Colorado; Lewis S. Nelson; Jeanmarie Perrone (Journal of Medical Toxicology, 2021)

Systematic Conservation Planning at an Ocean Basin Scale: Identifying a Viable Network of Deep-Sea Protected Areas in the North Atlantic and the Mediterranean - Magali Combes; Sandrine Vaz; Anthony Grehan; Telmo Morato; Sophie Arnaud-Haond; Carlos Dominguez-Carrió; Alan Fox; José Manuel González-Irusta; David Johnson; Oisín Callery; Andrew Davies; Laurence Fauconnet; et al. (Frontiers in Marine Science, 2021)
Designing conservation networks requires a well-structured framework for achieving essential objectives such as connectivity, replication or viability, and for considering local management and socioeconomic stakes. Although systematic conservation planning (SCP) approaches are increasingly used to inform such networks, their application remains challenging in large and poorly researched areas. This is especially the case in the deep sea, where SCP has rarely been applied, although growing awareness of the vulnerability of deep-sea ecosystems urges the implementation of conservation measures from local to international levels. This study aims to structure and evaluate a framework for SCP applicable to the deep sea, focusing on the identification of conservation priority networks for vulnerable marine ecosystems (VMEs), such as cold-water coral reefs, sponge grounds, or hydrothermal vents, and for key demersal fish species. Based on multi-objective prioritization, different conservation scenarios were investigated, allowing the impact of key elements such as connectivity and conservation cost to be evaluated. Our results show that continental margin slopes, the Mid-Atlantic Ridge, and deeper areas of large and productive shelves housing fishing grounds appeared as crucial zones for preserving the deep-sea biodiversity of the North Atlantic, and within the limitations imposed by the data available, of the Mediterranean. Using biologically-informed connectivity led to a more continuous and denser conservation network, without increasing the network size. Even when minimizing the overlap with socioeconomic activities, the inclusion of exploited areas was necessary to fulfil conservation objectives. Such areas included continental shelf fishing grounds for demersal fish species, and areas covered by deep-sea mining exploration contracts for hydrothermal vent communities. Covering 17% of the study area and protecting 55% of each feature on average, the identified priority network held a high conservation potential. However, these areas still suffer from poor protection, with 30% of them benefiting from some form of recognition and 11% only from protection against trawling. Integrating them into current marine spatial planning (MSP) discussions could foster the implementation of a basin-scale conservation network for the deep sea. Overall, this work established a framework for developing large-scale systematic planning, useful for managing Areas Beyond National Jurisdiction (ABNJ).

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Using the Schmahmann Syndrome Scale to Assess Cognitive Impairment in Young Adults with Metabolic Syndrome: a Hypothesis-Generating Report - Eithan Kotkowski; Larry R. Price; Cheasequah J. Blevins; Crystal G. Franklin; Mary D. Woolsey; Ralph A. DeFronzo; John Blangero; Ravindranath Duggirala; David C. Glahn; Jeremy D. Schmahmann; Peter T. Fox (The Cerebellum, 2021)

How complete are insect inventories? An assessment of the british butterfly database highlighting the influence of dynamic distribution shifts on sampling completeness - David Sánchez-Fernández; Richard Fox; Roger L. H. Dennis; Jorge M. Lobo (Biodiversity and Conservation, 2021)

TPEN exerts selective anti-leukemic efficacy in ex vivo drug-resistant childhood acute leukemia - Miguel Mendivil-Perez; Carlos Velez-Pardo; Gloria E. David-Yepes; Javier E. Fox; Marlene Jimenez-Del-Rio (BioMetals, 2021)

Latitudinal and environmental patterns of species richness in lizards and snakes across continental North America - Evan T. Whiting; David L. Fox (Journal of Biogeography, 2021)
Aim Little is known about the contributions of individual clades to the broader latitudinal diversity gradients of lizards and snakes in North America. Additionally, the environmental variables underpinning these patterns have not been extensively studied, nor have the relationships between squamate species richness and biome variety, a proxy for habitat heterogeneity. Here, we deconstruct the latitudinal diversity gradient of squamates and investigate lizard and snake species richness in relation to environmental gradients and biomes across continental North America. Location North America, excluding islands. Taxon Squamata (lizards and snakes). Methods We collated a suite of environmental variables ( n = 10) and squamate species ranges ( n = 1,152) in an equal‐area grid system (100 × 100 km cells) spanning continental North America. We deconstructed the latitudinal diversity gradient of squamates and examined species richness patterns for all lizards, all snakes and several individual squamate clades. We used multiple linear regressions to determine which environmental factors are most important for each squamate clade. Finally, we documented species richness within biomes and tested for correlations between species richness and biome variety. Results Squamates exhibit a strong latitudinal diversity gradient across continental North America. Snakes are more widespread and have a stronger gradient than lizards. Our multiple linear regression results indicate strong associations between species richness and environmental variables for all individual squamate clades analysed; temperature variables are strongly positively correlated with species richness. Biome variety is more strongly correlated with lizard species richness than snake species richness. Squamates are most species‐rich in tropical/subtropical forests, deserts and mangroves. Main conclusions Most snake clades in North America exhibit strong latitudinal diversity gradients, but only two lizard clades, Dactyloidae (anoles) and Gekkota (geckos), display strong gradients and thus drive the overall lizard pattern. Squamate clades differ in their responses to environmental gradients, as reflected by their species richness patterns, with warmer climates generally harboring more species. Lizards are more strongly associated with habitat heterogeneity than snakes are, consistent with results from previous studies. Squamates in more rapidly shifting biomes (e.g. deserts, mangroves) may face a greater risk of extinction from impending climate change.

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

A juvenile Tristan albatross (Diomedea dabbenena) on land at the Crozet Islands - Alexander L. Bond; Christopher Taylor; David Kinchin-Smith; Derren Fox; Emma Witcutt; Peter G. Ryan; Simon P. Loader; Henri Weimerskirch (Polar Biology, 2021)
Albatrosses and other seabirds are generally highly philopatric, returning to natal colonies when they achieve breeding age. This is not universal, however, and cases of extraordinary vagrancy are rare. The Tristan Albatross ( Diomedea dabbenena ) breeds on Gough Island in the South Atlantic Ocean, with a small population on Inaccessible Island, Tristan da Cunha, ca 380 km away. In 2015, we observed an adult male albatross in Gonydale, Gough Island, which had been ringed on Ile de la Possession, Crozet Islands in 2009 when it was assumed to be an immature Wandering Albatross ( D. exulans ). We sequenced 1109 bp of the cytochrome b mitochondrial gene from this bird, and confirmed it to be a Tristan Albatross, meaning its presence on Crozet 6 years previous, and nearly 5000 km away, was a case of prospecting behaviour in a heterospecific colony. Given the challenges in identifying immature Diomedea albatrosses, such dispersal events may be more common than thought previously.

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Retrospective analysis of the influence of environmental drivers on commercial stocks and fishing opportunities in the Irish Sea - Jacob W. Bentley; Natalia Serpetti; Clive J. Fox; Johanna J. Heymans; David G. Reid (Fisheries Oceanography, 2020)
Irish Sea fisheries have undergone considerable change in recent years following the decline of commercially important finfish stocks and their slow response to management's recovery plans. In 2015, the fishing industry called for a holistic exploration into the impact of environmental change and food web effects to identify the drivers underpinning stock dynamics. In this study, we identify correlations between large‐scale climatic indicators, temperature, primary and secondary productivity, and fish recruitment in the Irish Sea and incorporate them into an Ecopath with Ecosim food web model co‐created by scientists and fishers. Negative correlations were found between the North Atlantic Oscillation winter index (NAOw) and large zooplankton abundance and between the Atlantic Multidecadal Oscillation (AMO) and the recruitment of cod ( Gadus morhua ) and whiting ( Merlangius merlangus) . Using correlation analyses to direct the addition of environmental drivers to the Irish Sea ecosystem model improved the models fit against observed biomass and catch data and revealed the indirect impacts of environmental change as mitigated through trophic interactions. Model simulations suggest that historic environmental change suppressed the overall production of commercial finfish, limiting opportunities for the fishing industry, whilst also dampening the rate of stock recovery despite marked reductions in fishing effort. These results suggest that failure to account for ecosystem information may lead to misconceived expectations and flawed fisheries management; therefore, there is a need to operationalize ecosystem information through management procedures to support fisheries advice.

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

B- and O-isotopic compositions of tourmaline constrain late-stage magmatic volatile exsolution in Tasmanian tin-related granite systems - Wei Hong; Nathan Fox; David R. Cooke; Lejun Zhang; Mostafa Fayek (Mineralium Deposita, 2020)

Equilibrium sediment exchange in the earth’s critical zone: evidence from sediment fingerprinting with stable isotopes and watershed modeling - David Tyler Mahoney; Nabil Al Aamery; James Forrest Fox; Brenden Riddle; William Ford; Y. T. Wang (Journal of Soils and Sediments, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

An Efficient Multi-Objective Optimization Method for Use in the Design of Marine Protected Area Networks - Alan D. Fox; David W. Corne; C. Gabriela Mayorga Adame; Jeff A. Polton; Lea-Anne Henry; J. Murray Roberts (Frontiers in Marine Science, 2019)

Assessing nitrogen and phosphorus removal potential of five plant species in floating treatment wetlands receiving simulated nursery runoff - Jonathan T. Spangler; David J. Sample; Laurie J. Fox; Joseph P. Albano; Sarah A. White (Environmental Science and Pollution Research, 2019)

Data standards for model-informed drug development: an ISoP initiative - Andrijana Radivojevic; Brian Corrigan; Nicholas Downie; Robert Fox; Jill Fiedler-Kelly; Huan Liu; Murad Melhem; David Radke; Peter Schaefer; Jing Su; Maciej J. Swat; Nathan S. Teuscher; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Temperature influences habitat preference of coral reef fishes: Will generalists become more specialised in a warming ocean? - Paloma A. Matis; Jennifer M. Donelson; Stephen Bush; Rebecca J. Fox; David J. Booth (Global Change Biology, 2018)
Climate change is expected to pose a significant risk to species that exhibit strong behavioural preferences for specific habitat types, with generalist species assumed to be less vulnerable. In this study, we conducted habitat choice experiments to determine how water temperature influences habitat preference for three common species of coral reef damselfish (Pomacentridae) that differ in their levels of habitat specialisation. The lemon damselfish Pomacentrus moluccensis , a habitat specialist, consistently selected complex coral habitat across all temperature treatments (selected based on local average seasonal temperatures naturally experienced in situ: ambient winter 22°C; ambient summer 28°C; and elevated 31°C). Unexpectedly, the neon damselfish Pomacentrus coelestis and scissortail sergeant Abudefduf sexfasciatus , both of which have more generalist habitat associations, developed strong habitat preferences (for complex coral and boulder habitat, respectively) at the elevated temperature treatment (31°C) compared to no single preferred habitat at 22°C or 28°C. The observed shifts in habitat preference with temperature suggest that we may be currently underestimating the vulnerability of some habitat generalists to climate change and highlight that the ongoing loss of complex live coral through coral bleaching could further exacerbate resource overlap and species competition in ways not currently considered in climate change models.

Corrigendum: Composition of Dissolved Organic Matter in Pore Waters of Anoxic Marine Sediments Analyzed by 1H Nuclear Magnetic Resonance Spectroscopy - Christina A. Fox; Hussain A. Abdulla; David J. Burdige; James P. Lewicki; Tomoko Komada (Frontiers in Marine Science, 2018)

Rapid isolation and characterization of microsatellites in the critically endangered mountain bongo (Tragelaphus eurycerus isaaci) - Fraser J. Combe; Evelyn Taylor-Cox; Graeme Fox; Tommy Sandri; Nick Davis; Martin J. Jones; Bradley Cain; David Mallon; W. Edwin Harris (Journal of Genetics, 2018)

Composition of Dissolved Organic Matter in Pore Waters of Anoxic Marine Sediments Analyzed by 1H Nuclear Magnetic Resonance Spectroscopy - Christina A. Fox; Hussain A. Abdulla; David J. Burdige; James P. Lewicki; Tomoko Komada (Frontiers in Marine Science, 2018)

IL-11 facilitates a novel connection between RA joint fibroblasts and endothelial cells - Hatem A. Elshabrawy; Michael V. Volin; Abdul B. Essani; Zhenlong Chen; Iain B. McInnes; Katrien Van Raemdonck; Karol Palasiewicz; Shiva Arami; Mark Gonzalez; Hossam M. Ashour; Seung-jae Kim; Guofei Zhou; et al. (Angiogenesis, 2018)

‘Stick with your own kind, or hang with the locals?’ Implications of shoaling strategy for tropical reef fish on a range‐expansion frontline - Shannen M. Smith; Rebecca J. Fox; David J. Booth; Jennifer M. Donelson (Global Change Biology, 2018)
Range shifts of tropical marine species to temperate latitudes are predicted to increase as a consequence of climate change. To date, the research focus on climate‐mediated range shifts has been predominately dealt with the physiological capacity of tropical species to cope with the thermal challenges imposed by temperate latitudes. Behavioural traits of individuals in the novel temperate environment have not previously been investigated, however, they are also likely to play a key role in determining the establishment success of individual species at the range‐expansion forefront. The aim of this study was to investigate the effect of shoaling strategy on the performance of juvenile tropical reef fishes that recruit annually to temperate waters off the south east coast of Australia. Specifically, we compared body‐size distributions and the seasonal decline in abundance through time of juvenile tropical fishes that shoaled with native temperate species (‘mixed’ shoals) to those that shoaled only with conspecifics (as would be the case in their tropical range). We found that shoaling with temperate native species benefitted juvenile tropical reef fishes, with individuals in ‘mixed’ shoals attaining larger body‐sizes over the season than those in ‘tropical‐only’ shoals. This benefit in terms of population body‐size distributions was accompanied by greater social cohesion of ‘mixed’ shoals across the season. Our results highlight the impact that sociality and behavioural plasticity are likely to play in determining the impact on native fish communities of climate‐induced range expansion of coral reef fishes.

Using citizen science butterfly counts to predict species population trends - Emily B. Dennis; Byron J.T. Morgan; Tom M. Brereton; David B. Roy; Richard Fox (Conservation Biology, 2017)
Citizen scientists are increasingly engaged in gathering biodiversity information, but trade‐offs are often required between public engagement goals and reliable data collection. We compared population estimates for 18 widespread butterfly species derived from the first 4 years (2011–2014) of a short‐duration citizen science project (Big Butterfly Count [BBC]) with those from long‐running, standardized monitoring data collected by experienced observers (U.K. Butterfly Monitoring Scheme [UKBMS]). BBC data are gathered during an annual 3‐week period, whereas UKBMS sampling takes place over 6 months each year. An initial comparison with UKBMS data restricted to the 3‐week BBC period revealed that species population changes were significantly correlated between the 2 sources. The short‐duration sampling season rendered BBC counts susceptible to bias caused by interannual phenological variation in the timing of species’ flight periods. The BBC counts were positively related to butterfly phenology and sampling effort. Annual estimates of species abundance and population trends predicted from models including BBC data and weather covariates as a proxy for phenology correlated significantly with those derived from UKBMS data. Overall, citizen science data obtained using a simple sampling protocol produced comparable estimates of butterfly species abundance to data collected through standardized monitoring methods. Although caution is urged in extrapolating from this U.K. study of a small number of common, conspicuous insects, we found that mass‐participation citizen science can simultaneously contribute to public engagement and biodiversity monitoring. Mass‐participation citizen science is not an adequate replacement for standardized biodiversity monitoring but may extend and complement it (e.g., through sampling different land‐use types), as well as serving to reconnect an increasingly urban human population with nature.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

A complex history of introgression and vicariance in a threatened montane skink (Pseudemoia cryodroma) across an Australian sky island system - Margaret L. Haines; Devi Stuart-Fox; Joanna Sumner; Nick Clemann; David G. Chapple; Jane Melville (Conservation Genetics, 2017)

Synovial cellular and molecular markers in rheumatoid arthritis - M. Asif Amin; David A. Fox; Jeffrey H. Ruth (Seminars in Immunopathology, 2017)

Combating aggressive macrophyte encroachment on a typical Yangtze River lake: lessons from a long-term remote sensing study of vegetation - Qiang Jia; Lei Cao; Hervé Yésou; Claire Huber; Anthony David Fox (Aquatic Ecology, 2017)

Key actions towards the sustainable management of European geese - David A. Stroud; Jesper Madsen; Anthony D. Fox (Ambio, 2017)

Crowded skies: Conflicts between expanding goose populations and aviation safety - David R. Bradbeer; Camilla Rosenquist; Thomas Kjær Christensen; Anthony D. Fox (Ambio, 2017)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

Should I stay or should I go? Fitness costs and benefits of prolonged parent–offspring and sibling–sibling associations in an Arctic-nesting goose population - Mitch D. Weegman; Stuart Bearhop; Geoff M. Hilton; Alyn J. Walsh; Kaitlin M. Weegman; David J. Hodgson; Anthony David Fox (Oecologia, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Temperature and Residence Time Controls on an Estuarine Harmful Algal Bloom: Modeling Hydrodynamics and Alexandrium fundyense in Nauset Estuary - David K. Ralston; Michael L. Brosnahan; Sophia E. Fox; Krista D. Lee; Donald M. Anderson (Estuaries and Coasts, 2015)

Rapid growth and concerted sexual transitions by a bloom of the harmful dinoflagellate Alexandrium fundyense (Dinophyceae) - Michael L. Brosnahan; Lourdes Velo‐Suárez; David K. Ralston; Sophia E. Fox; Taylor R. Sehein; Alexi Shalapyonok; Heidi M. Sosik; Robert J. Olson; Donald M. Anderson (Limnology and Oceanography, 2015)
Transitions between life cycle stages by the harmful dinoflagellate Alexandrium fundyense are critical for the initiation and termination of its blooms. To quantify these transitions in a single population, an Imaging FlowCytobot (IFCB), was deployed in Salt Pond (Eastham, Massachusetts), a small, tidally flushed kettle pond that hosts near annual, localized A. fundyense blooms. Machine‐based image classifiers differentiating A. fundyense life cycle stages were developed and results were compared to manually corrected IFCB samples, manual microscopy‐based estimates of A. fundyense abundance, previously published data describing prevalence of the parasite Amoebophrya , and a continuous culture of A. fundyense infected with Amoebophrya . In Salt Pond, a development phase of sustained vegetative division lasted approximately 3 weeks and was followed by a rapid and near complete conversion to small, gamete cells. The gametic period (∼3 d) coincided with a spike in the frequency of fusing gametes (up to 5% of A. fundyense images) and was followed by a zygotic phase (∼4 d) during which cell sizes returned to their normal range but cell division and diel vertical migration ceased. Cell division during bloom development was strongly phased, enabling estimation of daily rates of division, which were more than twice those predicted from batch cultures grown at similar temperatures in replete medium. Data from the Salt Pond deployment provide the first continuous record of an A. fundyense population through its complete bloom cycle and demonstrate growth and sexual induction rates much higher than are typically observed in culture.

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Multiplication of microbes below 0.690 water activity: implications for terrestrial and extraterrestrial life - Andrew Stevenson; Jürgen Burkhardt; Charles S. Cockell; Jonathan A. Cray; Jan Dijksterhuis; Mark Fox‐Powell; Terence P. Kee; Gerhard Kminek; Terry J. McGenity; Kenneth N. Timmis; David J. Timson; Mary A. Voytek; et al. (Environmental Microbiology, 2015)
Summary Since a key requirement of known life forms is available water (water activity; a w ), recent searches for signatures of past life in terrestrial and extraterrestrial environments have targeted places known to have contained significant quantities of biologically available water. However, early life on E arth inhabited high‐salt environments, suggesting an ability to withstand low water‐activity. The lower limit of water activity that enables cell division appears to be ∼ 0.605 which, until now, was only known to be exhibited by a single eukaryote, the sugar‐tolerant, fungal xerophile X eromyces bisporus . The first forms of life on E arth were, though, prokaryotic. Recent evidence now indicates that some halophilic A rchaea and B acteria have water‐activity limits more or less equal to those of X . bisporus . We discuss water activity in relation to the limits of E arth's present‐day biosphere; the possibility of microbial multiplication by utilizing water from thin, aqueous films or non‐liquid sources; whether prokaryotes were the first organisms able to multiply close to the 0.605‐a w limit; and whether extraterrestrial aqueous milieux of ≥ 0.605 a w can resemble fertile microbial habitats found on Earth.

Erratum to: Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; John Blangero; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Interpreting seasonal range shifts in migratory birds: a critical assessment of ‘short-stopping’ and a suggested terminology - Johan Elmberg; Rebecca Hessel; Anthony David Fox; Lars Dalby (Journal of Ornithology, 2014)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Influence of age, sex and genetic factors on the human brain - D. Reese McKay; Emma E. M. Knowles; Anderson A. M. Winkler; Emma Sprooten; Peter Kochunov; Rene L. Olvera; Joanne E. Curran; Jack W. Kent; Melanie A. Carless; Harald H. H. Göring; Thomas D. Dyer; Ravi Duggirala; et al. (Brain Imaging and Behavior, 2014)

Seasonality drives global‐scale diversity patterns in waterfowl ( A nseriformes) via temporal niche exploitation - Lars Dalby; Brian J. McGill; Anthony David Fox; Jens‐Christian Svenning (Global Ecology and Biogeography, 2014)
Aim Birds (class A ves) overall follow the expected latitudinal gradient in species richness. However, there is a poorly understood secondary peak in bird richness at about 45° N latitude, at least in N orth A merica. Waterfowl ( A nseriformes) species richness conforms to this secondary peak, yet this group is commonly excluded from bird species richness studies and consequently the drivers of waterfowl richness are poorly understood. Here, we explore the drivers of waterfowl richness on a global scale, emphasizing the secondary peak. Location Global. Methods We mapped total waterfowl species richness for the breeding and non‐breeding seasons. Considering a wide range of potential environmental drivers (climate, productivity and habitat), we initially ran univariate ordinary least squares models for the candidate set of predictors. We then used regression trees ( RT ) to multivariately assess their importance for the richness pattern while allowing for nonlinear and non‐stationary processes. Results We found seasonal variability in plant productivity (measured by the normalized difference vegetation index, NDVI ) to be the most important predictor of breeding season richness in both univariate regressions and multivariate RT models. For the non‐breeding season, winter actual evapotranspiration ( AET ) was the best predictor. In the regions of highest richness, including the secondary mid‐latitude peak, an overwhelming portion of the species were migratory species. Main conclusions Predictors commonly used to explain the large‐scale richness patterns of birds, such as annual AET or annual NDVI explained little of the variation in richness in A nseriformes. Instead, measures reflecting intra‐annual variability and seasonal productivity in the relevant season were the best predictors. This finding, combined with the high proportion of migrants in the richness peaks, strongly suggests that the patterns of richness in A nseriformes reflect the group's exploitation of seasonal environmental variability via short‐ and long‐distance migration, i.e. temporal niche exploitation at an annual and global scale.

Evaluation of ionic liquids on phototrophic microbes and their use in biofuel extraction and isolation - Katherine S. Lovejoy; Lauren E. Davis; Lisa M. McClellan; Antonietta M. Lillo; John D. Welsh; Emily N. Schmidt; Claire K. Sanders; Alexander J. Lou; David T. Fox; Andrew T. Koppisch; Rico E. Del Sesto (Journal of Applied Phycology, 2013)

Seasonal variation in Eurasian Wigeon Anas penelope sex and age ratios from hunter-based surveys - Kevin Kuhlmann Clausen; Lars Dalby; Peter Sunde; Thomas Kjær Christensen; Bjarke Egelund; Anthony David Fox (Journal of Ornithology, 2013)

The fossil history of G révy's zebra ( E quus grevyi ) in equatorial East A frica - J. Tyler Faith; Christian A. Tryon; Daniel J. Peppe; David L. Fox (Journal of Biogeography, 2013)
Aim Within the last several decades, G révy's zebra ( E quus grevyi ) has undergone a massive reduction in geographical range and population size, largely as the result of human impacts. To place its recent decline in a deeper prehistoric context, and to understand the factors mediating its range and abundance over geological time frames, this study examines the fossil history of G révy's zebra in equatorial E ast A frica. Location Equatorial E ast A frica. Methods Presence/absence data for ungulates recovered from fossil sites spanning the last c . 400,000 years in K enya and E thiopia were compiled from the literature and from previously unreported palaeontological sites. Associations between G révy's zebra and other taxa were examined using principal coordinates analysis and non‐random species pairs were identified using a Bayesian approach. Changes in rainfall were reconstructed using the average hypsodonty index of ungulate species from fossil assemblages. Results G révy's zebra was common during dry phases of the P leistocene and was found to the south and west of its historical range, coinciding with an expansion of arid grasslands. At the onset of the H olocene, G révy's zebra was extirpated from southern K enya and almost completely disappeared from the fossil record. G révy's zebra was associated with several specialized grazers that became extinct by the end of the Pleistocene. These extinctions and the decline of G révy's zebra from the P leistocene to the H olocene are explained by increased precipitation and the consequent loss of arid grasslands at the P leistocene– H olocene transition. G révy's zebra is never associated with domestic livestock, unlike the widespread plains zebra. Main conclusions Grévy's zebra thrived in equatorial E ast A frica during periods of the P leistocene when environmental conditions favoured an expansion of arid grasslands. Environmental change across the P leistocene– H olocene transition contributed to decreases in the range size and abundance of G révy's zebra, setting the stage for the anthropogenic decline observed in recent decades. The spread of pastoralists in the middle H olocene may have additionally contributed to its prehistoric decline. Contemporary climate change warrants further consideration in planning for the long‐term survival of G révy's zebra.

Varying energetic costs of Brent Geese along a continuum from aquatic to agricultural habitats: the importance of habitat-specific energy expenditure - Kevin Kuhlmann Clausen; Preben Clausen; Anthony David Fox; Casper Cæsar Fælled; Jesper Madsen (Journal of Ornithology, 2013)

Earlier spring staging in Iceland amongst Greenland White-fronted Geese Anser albifrons flavirostris achieved without cost to refuelling rates - Anthony D. Fox; Hugh Boyd; Alyn J. Walsh; David A. Stroud; Jens Nyeland; Ruth L. Cromie (Hydrobiologia, 2012)

Neanderthal medics? Evidence for food, cooking, and medicinal plants entrapped in dental calculus - Karen Hardy; Stephen Buckley; Matthew J. Collins; Almudena Estalrrich; Don Brothwell; Les Copeland; Antonio García-Tabernero; Samuel García-Vargas; Marco Rasilla; Carles Lalueza-Fox; Rosa Huguet; Markus Bastir; et al. (The Science of Nature, 2012)

A comparison of two microbial detection methods used in aseptic processing of musculoskeletal allograft tissues - Jeremy A. Dennis; Octavio V. Martinez; David C. Landy; Theodore I. Malinin; Paul R. Morris; William P. Fox; Billy E. Buck; H. Thomas Temple (Cell and Tissue Banking, 2011)

Phase locking, the Moran effect and distance decay of synchrony: experimental tests in a model system - Jeremy W. Fox; David A. Vasseur; Stephen Hausch; Jodie Roberts (Ecology Letters, 2011)
Ecology Letters (2011) 14: 163–168 Abstract Spatially separated populations of many species fluctuate synchronously. Synchrony typically decays with increasing interpopulation distance. Spatial synchrony, and its distance decay, might reflect distance decay of environmental synchrony (the Moran effect), and/or short‐distance dispersal. However, short‐distance dispersal can synchronize entire metapopulations if within‐patch dynamics are cyclic, a phenomenon known as phase locking. We manipulated the presence/absence of short‐distance dispersal and spatially decaying environmental synchrony and examined their separate and interactive effects on the synchrony of the protist prey species Tetrahymena pyriformis growing in spatial arrays of patches (laboratory microcosms). The protist predator Euplotes patella consumed Tetrahymena and generated predator–prey cycles. Dispersal increased prey synchrony uniformly over both short and long distances, and did so by entraining the phases of the predator–prey cycles. The Moran effect also increased prey synchrony, but only over short distances where environmental synchrony was strongest, and did so by increasing the synchrony of stochastic fluctuations superimposed on the predator–prey cycle. Our results provide the first experimental demonstration of distance decay of synchrony due to distance decay of the Moran effect. Distance decay of the Moran effect likely explains distance decay of synchrony in many natural systems. Our results also provide an experimental demonstration of long‐distance phase locking, and explain why cyclic populations provide many of the most dramatic examples of long‐distance spatial synchrony in nature.

Inbreeding-environment interactions for fitness: complex relationships between inbreeding depression and temperature stress in a seed-feeding beetle - Charles W. Fox; R. Craig Stillwell; William G. Wallin; Carrie L. Curtis; David H. Reed (Evolutionary Ecology, 2011)

Pattern-based information extraction from pathology reports for cancer registration - Giulio Napolitano; Colin Fox; Richard Middleton; David Connolly (Cancer Causes & Control, 2010)

Anatomical Global Spatial Normalization - Jack L. Lancaster; Matthew D. Cykowski; David Reese McKay; Peter V. Kochunov; Peter T. Fox; William Rogers; Arthur W. Toga; Karl Zilles; Katrin Amunts; John Mazziotta (Neuroinformatics, 2010)

Interactive Decision Support for Risk Management: a Qualitative Evaluation in Cancer Genetic Counselling Sessions - David W. Glasspool; Ayelet Oettinger; Dejana Braithwaite; John Fox (Journal of Cancer Education, 2010)

Planning Future Strategies for Domestic and International NeuroAIDS Research, July 24–25, 2008 - Jeymohan Joseph; David Clifford; Steven D. Douglas; Howard Fox; Howard E. Gendelman; Francisco Gonzalez-Scarano; Igor Grant; Eugene Major; Justin McArthur (Journal of Neuroimmune Pharmacology, 2009)

Rapid Evolution in the Wild: Changes in Body Size, Life‐History Traits, and Behavior in Hunted Populations of the Japanese Mamushi Snake - KIYOSHI SASAKI; STANLEY F. FOX; DAVID DUVALL (Conservation Biology, 2009)
Rapid evolution caused by human exploitation of wildlife is not usually addressed in studies of the impacts of such exploitation despite its direct relevance to population persistence. Japanese mamushi ( Gloydius blomhoffii ), an endemic venomous snake of the Japanese archipelago, has been heavily hunted by humans, and many populations appear to be declining or are already extirpated. We compared local populations that have been hunted regularly with populations that have not been hunted. Mamushi in hunted populations were smaller, had fewer vertebrae, produced more and smaller offspring, had increased reproductive effort among smaller females, and in nature fled at greater distances from an approaching human and were less defensive than mamushi in unhunted populations, as predicted from life‐history theory. Heritability estimates for body size, number of vertebrae, and antipredator behavior were statistically significant, and neonates from hunted sites showed the same distribution of altered characters (compared with those from unhunted sites) as adults. Thus, distribution of the divergent trait between hunted and unhunted sites appeared in part to be genetically based, which suggests rapid evolution to human predation pressures. Trait distributions in hunted populations probably deviate from naturally (as opposed to anthropogenically) selected optima and, therefore, may have long‐term negative repercussions on population persistence. Because rapid evolution affects a suite of parameters that characterize exploited populations, accurate understanding of the impacts of exploitation and effective resource management and conservation can only be achieved if evolutionary consequences are considered explicitly.

The latitudinal gradient of beta diversity in relation to climate and topography for mammals in North America - Hong Qian; Catherine Badgley; David L. Fox (Global Ecology and Biogeography, 2009)
Aim Spatial turnover of species, or beta diversity, varies in relation to geographical distance and environmental conditions, as well as spatial scale. We evaluated the explanatory power of distance, climate and topography on beta diversity of mammalian faunas of North America in relation to latitude. Location North America north of Mexico. Methods The study area was divided into 313 equal‐area quadrats (241 × 241 km). Faunal data for all continental mammals were compiled for these quadrats, which were divided among five latitudinal zones. These zones were comparable in terms of latitudinal and longitudinal span, climatic gradients and elevational gradients. We used the natural logarithm of the Jaccard index (ln J ) to measure species turnover between pairs of quadrats within each latitudinal zone. The slope of ln J in relation to distance was compared among latitudinal zones. We used partial regression to partition the variance in ln J into the components uniquely explained by distance and by environmental differences, as well as jointly by distance and environmental differences. Results Mammalian faunas of North America differ more from each other at lower latitudes than at higher latitudes. Regression models of ln J in relation to distance, climatic difference and topographic difference for each zone demonstrated that these variables have high explanatory power that diminishes with latitude. Beta diversity is higher for zones with higher mean annual temperature, lower seasonality of temperature and greater topographic complexity. For each latitudinal zone, distance and environmental differences explain a greater proportion of the variance in ln J than distance, climate or topography does separately. Main conclusions The latitudinal gradient in beta diversity of North American mammals corresponds to a macroclimatic gradient of decreasing mean annual temperature and increasing seasonality of temperature from south to north. Most of the variance in spatial turnover is explained by distance and environmental differences jointly rather than distance, climate or topography separately. The high predictive power of geographical distance, climatic conditions and topography on spatial turnover could result from the direct effects of physical limiting factors or from ecological and evolutionary processes that are also influenced by the geographical template.

Assessing for genetic and environmental effects on ruminant feed quality in barley (Hordeum vulgare) - Glen P. Fox; Jan Bowman; Alison Kelly; Andy Inkerman; David Poulsen; Robert Henry (Euphytica, 2008)

Direct versus indirect methods of quantifying herbivore grazing impact on a coral reef - Rebecca J. Fox; David R. Bellwood (Marine Biology, 2008)

Environmental fluctuations can stabilize food web dynamics by increasing synchrony - David A. Vasseur; Jeremy W. Fox (Ecology Letters, 2007)
Natural food webs are species‐rich, but classical theory suggests that they should be unstable and extinction‐prone. Asynchronous fluctuations in the densities of competing consumers can stabilize food web dynamics in constant environments. However, environmental fluctuations often synchronize dynamics in nature. Using the same ‘diamond‐shape’ food web model first used to demonstrate the stabilizing effects of asynchrony in constant environments, we show that weak‐to‐moderate environmentally induced fluctuations in consumer mortality rates stabilize food webs while disrupting asynchrony. Synchrony actually promotes stability because: (i) synchronous declines in consumer density reduce the maximum abundance of top predators and (ii) resource competition quickly converts synchronous increases in consumer density into synchronous declines. These results are robust to details of food web topology and the implementation of environmental fluctuations. The fluctuation strengths that enhance stability are within the range experienced naturally by many species, suggesting that stabilization via environmental fluctuations is a realistic possibility.

Government targets for protected area management: will threatened butterflies benefit? - Harriet Davies; Tom M. Brereton; David B. Roy; Richard Fox (Biodiversity and Conservation, 2007)

Genetic variation in prehistoric Sardinia - David Caramelli; Cristiano Vernesi; Simona Sanna; Lourdes Sampietro; Martina Lari; Loredana Castrì; Giuseppe Vona; Rosalba Floris; Paolo Francalacci; Robert Tykot; Antonella Casoli; Jaume Bertranpetit; et al. (Human Genetics, 2007)

Hot Rocks: The Greatest Hits of the Fossil Record - David L. Fox (Journal of Mammalian Evolution, 2007)

Impacts of climate warming and habitat loss on extinctions at species' low‐latitude range boundaries - ALDINA M. A. FRANCO; JANE K. HILL; CLAUDIA KITSCHKE; YVONNE C. COLLINGHAM; DAVID B. ROY; RICHARD FOX; BRIAN HUNTLEY; CHRIS D. THOMAS (Global Change Biology, 2006)
Polewards expansions of species' distributions have been attributed to climate warming, but evidence for climate‐driven local extinctions at warm (low latitude/elevation) boundaries is equivocal. We surveyed the four species of butterflies that reach their southern limits in Britain. We visited 421 sites where the species had been recorded previously to determine whether recent extinctions were primarily due to climate or habitat changes. Coenonympha tullia had become extinct at 52% of study sites and all losses were associated with habitat degradation. Aricia artaxerxes was extinct from 50% of sites, with approximately one‐third to half of extinctions associated with climate‐related factors and the remainder with habitat loss. For Erebia aethiops (extinct from 24% of sites), approximately a quarter of the extinctions were associated with habitat and three‐quarters with climate. For Erebia epiphron , extinctions (37% of sites) were attributed mainly to climate with almost no habitat effects. For the three species affected by climate, range boundaries retracted 70–100 km northwards ( A. artaxerxes , E. aethiops ) and 130–150 m uphill ( E. epiphron ) in the sample of sites analysed. These shifts are consistent with estimated latitudinal and elevational temperature shifts of 88 km northwards and 98 m uphill over the 19‐year study period. These results suggest that the southern/warm range margins of some species are as sensitive to climate change as are northern/cool margins. Our data indicate that climate warming has been of comparable importance to habitat loss in driving local extinctions of northern species over the past few decades; future climate warming is likely to jeopardize the long‐term survival of many northern and mountain species.

The distributions of a wide range of taxonomic groups are expanding polewards - RACHAEL HICKLING; DAVID B. ROY; JANE K. HILL; RICHARD FOX; CHRIS D. THOMAS (Global Change Biology, 2006)
Evidence is accumulating of shifts in species' distributions during recent climate warming. However, most of this information comes predominantly from studies of a relatively small selection of taxa (i.e., plants, birds and butterflies), which may not be representative of biodiversity as a whole. Using data from less well‐studied groups, we show that a wide variety of vertebrate and invertebrate species have moved northwards and uphill in Britain over approximately 25 years, mirroring, and in some cases exceeding, the responses of better‐known groups.

The Anthracen-9-ylmethyloxy Unit: An Underperforming Motif Within the Fluorescent PET (Photoinduced Electron Transfer) Sensing Framework - David C. Magri; John F. Callan; A. Prasanna de Silva; David B. Fox; Nathan D. McClenaghan; K. R. A. Samankumara Sandanayake (Journal of Fluorescence, 2005)

DETECTION OF NORTH PACIFIC RIGHT WHALE ( EUBALAENA JAPONICA ) CALLS IN THE GULF OF ALASKA - David K. Mellinger; Kathleen M. Stafford; Sue E. Moore; Lisa Munger; Christopher G. Fox (Marine Mammal Science, 2004)

SEASONAL OCCURRENCE OF SPERM WHALE ( PHYSETER MACROCEPHALUS ) SOUNDS IN THE GULF OF ALASKA, 1999–2001 - David K. Mellinger; Kathleen M. Stafford; Christopher G. Fox (Marine Mammal Science, 2004)
A bstract An acoustic survey for sperm whales was conducted in the Gulf of Alaska. Six autonomous hydrophones continuously recorded sound signals below 500 Hz from October 1999 to May 2001. After recovery, recordings were processed using an automatic process to detect usual clicks of sperm whales. The detection algorithm equalized background noise, summed the data in a frequency band, and then used autocorrelation to detect the whales' highly regular clicks. Detections were checked manually, revealing that 98% of detections did contain clicks. Results indicate that sperm whales are present in the Gulf of Alaska year‐round; this result extends what is known from whaling data, which were gathered principally in summer. Sperm whales were more common in summer than winter by a factor of roughly two, and occurred less often at the westernmost site surveyed (52°N, 157°W) than elsewhere in the Gulf. This is the first study of sperm whales based exclusively on remote acoustic sensing. This methodology is feasible because sperm whale clicks extend to frequencies (∼100 Hz) low enough to be recorded by low‐sample‐rate instruments that operate continuously, and because the detection algorithm has a low false‐detection rate. The methodology may be replicated to facilitate comparisons between different time periods and geographic regions.

North Sea cod and climate change – modelling the effects of temperature on population dynamics - Robin A. Clark; Clive J. Fox; David Viner; Matthew Livermore (Global Change Biology, 2003)
In order to examine the likely impacts of climate change on fish stocks, it is necessary to couple the output from large‐scale climate models to fisheries population simulations. Using projections of future North Sea surface temperatures for the period 2000–2050 from the Hadley General Circulation Model, we estimate the likely effects of climate change on the North Sea cod population. Output from the model suggests that increasing temperatures will lead to an increased rate of decline in the North Sea cod population compared with simulations that ignore environmental change. Although the simulation developed here is relatively simplistic, we demonstrate that inclusion of environmental factors in population models can markedly alter one's perception of how the population will behave. The development of simulations incorporating environment effects will become increasingly important as the impacts of climate change on the marine ecosystem become more pronounced.

Development and Validation of a Herring Gull Embryo Toxicokinetic Model for PCBs - Ken G. Drouillard; Ross J. Norstrom; Glen A. Fox; Andy Gilman; David B. Peakall (Ecotoxicology, 2003)

Ecological biogeography of North American mammals: species density and ecological structure in relation to environmental gradients - Catherine Badgley; David L. Fox (Journal of Biogeography, 2000)
Aim To evaluate the relationship of climate and physiography to species density and ecological diversity of North American mammals. Location North America, including Mexico and Central America. Methods Species density, size structure and trophic structure of mammalian faunas and nine environmental variables were documented for quadrats covering the entire continent. Spatial autocorrelation of species density and the environmental variables illustrated differences in their spatial structure at the continental scale. We used principal component analysis to reduce the dimensionality of the climatic variables, linear multiple regression to determine which environmental variables best predict species density for the continent and several regions of the continent, and canonical ordination to evaluate how well the environmental variables predict ecological structure of mammalian faunas over North America. Results In the best regression model, five environmental variables, representing seasonal extremes of temperature, annual energy and moisture, and elevation, predicted 88% of the variation in species density for the whole continent. Among different regions of North America, the environmental variables that predicted species density vary. Changes in the size and trophic structure of mammalian faunas accompany changes in species density. Redundancy analysis demonstrated that environmental variables representing winter temperature, frostfree period, potential and actual evapotranspiration, and elevation account for 77% of the variation in ecological structure. Main conclusions The latitudinal gradient in mammalian species density is strong, but most of it is explained by variation in the environmental variables. Each ecological category peaks in species richness under particular environmental conditions. The changes of greatest magnitude involve the smallest size categories ( Much of the spatial pattern is consistent with ecological sorting of species ranges along environmental gradients, but differential rates of speciation and extinction also may have shaped the ecological diversity of extant North American mammals.

A Genomically Modified Marker Strain of Escherichia coli - David Ammons; Joanne Rampersad; George E. Fox (Current Microbiology, 1998)

The effects of simulated spring goose grazing on the growth rate and protein content of Phleum pratense leaves - A. D. Fox; Jens N. Kristiansen; David A. Stroud; Hugh Boyd (Oecologia, 1998)

SEASONAL VARIATION IN RECEPTION OF FIN WHALE CALLS AT FIVE GEOGRAPHIC AREAS IN THE NORTH PACIFIC - Sue E. Moore; Kathleen M. Stafford; Marilyn E. Dahlheim; Christopher G. Fox; Howard W. Braham; Jeffrey J. Polovina; David E. Bain (Marine Mammal Science, 1998)

Desertification Evaluated Using an Integrated Environmental Assessment Model - David Mouat; Judith Lancaster; Timothy Wade; James Wickham; Carl Fox; William Kepner; Timothy Ball (Environmental Monitoring and Assessment, 1997)

Rabbit linkage group VIII: The alleles of the prt gene - David C. Usher; Boonbungearn Cogburn; Richard R. Fox (Biochemical Genetics, 1983)

R68.45 mediated chromosomal gene transfer in Agrobacterium tumefaciens - Julie Bryan; Nasim Saeed; David Fox; G. R. K. Sastry (Archives of Microbiology, 1982)

The soluble citric acid cycle enzymes ofDrosophila melanogaster. II. Tissue and intracellular distribution of aconitase and NADP-dependent isocitrate dehydrogenase - David J. Fox; Marianne Conscience-Egli; Erika Abächerli (Biochemical Genetics, 1972)

The soluble citric acid cycle enzymes of Drosophila melanogaster. I. Genetics and ontogeny of NADP-linked isocitrate dehydrogenase - David J. Fox (Biochemical Genetics, 1971)